Cultural Attitudes Toward Weight, Diet, and Physical Activity Among Overweight African American Girls - Josephine E. A. Boyington, PhD, MPH, RN; Lori Carter-Edwards, PhD, MPH; Mark Piehl, MD, MPH; Jeanne Hutson, MPH, RN, RD, CDE, BC-ADM; Debbe Langdon, RN, BSN, CDE; Shilpa McManus, MPH (Centers for Disease Control and Prevention, 2008)
IntroductionThe growing epidemic of childhood obesity has led to an increasing focus on strategies for prevention. However, little is known about attitudes and perceptions toward weight, diet, and physical activity among American youth, and particularly among young African American females. This pilot study sought to qualitatively explore cultural attitudes and perceptions toward body image, food, and physical activity among a sample of overweight African American girls.MethodsWe recruited 12 overweight girls, aged 12 to 18 years, from a hospital-based pediatric diabetes screening and prevention program. Five semistructured group interviews were conducted to explore attitudes on weight, diet, and physical activity. Sessions averaged 1 hour and were conducted by trained interviewers. Data were transcribed and evaluated for content and relevant themes.ResultsThe following themes emerged: weight and body size preferences were primarily determined by the individual and her immediate social circle and were less influenced by opinions of those outside of the social circle; food choices depended on texture, taste, appearance, and context more than on nutritional value; engagement in recreational physical activity was influenced by time constraints from school and extracurricular activities and by neighborhood safety; participation in structured exercise was limited because of the cost and time related to maintenance of personal aesthetics (hair and nails); and celebrities were not perceived as role models for diet and physical activity habits.ConclusionIn this sample of girls, the findings imply that perceptions of weight and healthy lifestyle behaviors are largely determined by environmental and personal influences. These factors should be considered in the development of healthy-weight interventions for African American girls.